Is there an illocutionary act of assertion? - Chankova, Mariya (English Studies at NBU, 2015)
This contribution analyzes Cappelen’s No-Assertion view arguing that, although appealing, the No-Assertion view is based on a questionable premise, namely, that assertions are sayings. Austin’s notions of locution and saying are examined, in order to show that illocutionary acts concern aspects not covered by either of the previous two terms. Following a reconstructed definition of illocutionary act from Austin’s writings, I suggest that assertion is an illocutionary act, in that it takes effect after it is taken up by a hearer. I further suggest that in this respect the game analogy fails with regard to assertion, since no rules of the constitutive kind or norms can intrinsically define this act. This proposal is based on the idea that illocutionary act analysis should dispose of any preoccupations with propositions. It argues that expressing propositions was not originally and should not be at the core of speech act theoretic problematic.